Andy Letcher, Shroom: A Cultural History of the Magic Mushroom - Harvey, Graham (Journal for the study of religion, nature and culture, 2007)
Andy Letcher, Shroom: A Cultural History of the Magic Mushroom (New York: Ecco, 2007), 384 pp. Pbk. $25.95, ISBN 0-06-082828-5.